BACTERIAL POPULATION AND ENZYEMIC ACTIVITY OF LIGNOSELLULOLITIC BACTERIA BIOCATALIS - F. D., Prabowo; Cakra, I G. L. O.; Mudita, I M. (Jurnal Peternakan Tropika; Vol 9 No 1 (2021): Vol. 9 No. 1 Tahun 2021; January - april, 2021)
This study aims to determine the quality of biocatalysts produced using lignocellulolytic bacteria singly and to determine the best bacterial biocatalysts. This research study was conducted at the Sesetan Laboratory and Animal Nutrition and Forage Laboratory of the Faculty of Animal Husbandry, Udayana University which was conducted from June to September 2019. The design used was a completely randomized design (CRD) consisting of 6 treatments, namely biocatalysts without lignocellulolytic bacteria as control (B0). , biocatalysts use Bacillus substilis BR4LG (B1), biocatalysts use Bacillus substilis BR2CL (B2), biocatalysts use Aneurinibacillus sp. BT4LS (B3), a biocatalyst using Bacillus sp. BT3CL (B4), and biocatalysts using Bacillus sp. BT8XY (B5). Each treatment has 3 replications. The variables observed were the bacterial population and the activity of the enzymes ligninase, endoglucanase, exogilanase and xylanase, respectively at the incubation time of 30 minutes, 1 hour, 3 hours and 6 hours. The results showed that the use of lignocellulolytic bacteria could improve the quality of biocatalysts, which was reflected in the bacterial population and the activity of the enzymes ligninase, endoglucanase, exogilanase, and xylanase. The best bacterial biocatalyst in this study was Bacillus substilis BR2CL (B2) because it was able to improve the quality of the biocatalyst, especially the bacterial population, the activity of the exogucanase enzyme in the incubation period of 30 minutes, 1 hour, 3 hours, and 6 hours, and xylanase activity in the 6 hour incubation period. Keywords : lignocellulolytic bacterial biocatalyst, bacterial population, and enzyme activity